Sustainable Agriculture Reviews 28 Ecology for Agriculture (Sustainable Agriculture Reviews,, 2018)
This book presents ecological principles and applications of managing biodiversity in agriculture to decrease pesticide use and produce safe food. Major topics include ecosystem services biological pest control, conservation agriculture, drought stress, and soil biodiversity, carbon and fertilisation.